The answer would be: A- Reflect the graph of f across the y-axis.
In this question, the function would be:
f(x)= [tex] \sqrt{x} [/tex]
g(x)= [tex] \sqrt{-x} [/tex]
The difference between the two functions would be the g(x) have a minus sign inside the root. We can conclude that the transformation causing the x--->-x'.
When you reflect a function on y-axis, the value of x would be -x. That means a point that was (1, 1) would become (-1, 1). The changes would look like this
x=-x'
f(x)= [tex] \sqrt{x} [/tex]
f(x)= [tex] \sqrt{-x'} [/tex]